The meniscotibial ligament does exist: An anatomic and histological description - Shi-Tang Song; Xin-Jie Wang; Jing Ye; Ji-Ying Zhang; You-Rong Chen; Yi-Fan Song; Jia-Kuo Yu; Bing-Bing Xu (Elsevier, 2024)
Purpose: To describe the anatomical and histological characteristics of the human MTL (meniscotibial ligament) that keeps the meniscus stable and are rarely discussed. Study design: Descriptive laboratory study. Methods: In total, six fresh-frozen adult cadaver knees were dissected, and the dissection protocol were designed by two experienced anatomy professors. The anatomical morphology of MTL was observed. The main anatomical specimens included meniscus, tibial plateau, MTL. The osteotome was used to excise the portion of the tibial plateau, which could obtain the complex including partial meniscus, MTL, and a tibial fragment. A histopathologic study was performed by two experienced pathologists. Results: Macroscopically, the MTL could be divided into two parts: medial meniscotibial ligament (MMTL)and lateral meniscotibial ligament (LMTL). The MMTL is distributed continuously, whereas the LMTL is discontinuous on the tibial plateau. The average length from the tibial attachment of the LMTL to the articular surface was 19 ± 1.0mm (mean ± SD). The average length from the tibial attachment of the MMTL to the articular surface was 10 ± 1.2 mm (mean ± SD). Microscopy of the MTL showed that the MTL is a ligamentous tissue, composed of a network of oriented collagenous fibers. Conclusions: In all knees, the MTL was inserted on the outer edge of the meniscus, attaching to the tibia below the level of articular cartilage, which was key to maintaining the rotational stability of knee and the meniscus in the physiological position on the tibial plateau. Histological analysis of this ligament demonstrated that the MTL is a veritable ligamentous structure, which is made up of collagen type I-expressing fibroblasts. Clinical relevance: This article contributes to the understanding of the anatomical and histological characteristics of the MTL. It is beneficial to promote the development of relevant surgical techniques for the MTL lesion.